?-Carotene Bleaching and ABTS Cation Radical Scavenging Activities of the Extracts from Different Parts of In Vivo and In Vitro Raised Pictacia lentiscus L. - Tilkat, L. Engin; Suzerer, Veysel; Izol, Ebubekir; Ertas, Abdulselam; Asan, Hilal Surmus; Yilmaz, Mustafa Abdullah; Onay, Ahmet (Springer, 2016)
[No abstract available]
World Congress on In Vitro Biology -- JUN 11-15, 2016 -- San Diego, CA